The under-recognition of the significance of social class conceptions of education in Piketty's Capital. Issue 6 (17th August 2016) - Dale, Roger
Abstract: Piketty's Capital has created enormous interest around the world, not least in educational circles. One reason for this may be his readiness to refer, in a book largely focused on economic history, to the ways that education has, and might, contribute to better and more equal social outcomes. This article welcomes this approach, but argues that Piketty's suggestions remain somewhat limited due to his adherence to a more or less distributional, rather than relational, approach, and then sets out to address this issue by arguing that the assumption that it is the distribution of credentials which accounts for their contribution is mistaken. Instead, the article advances arguments which recognize the separate contributions of the content of credentials, and their valorization. The main focus of this article is thus on the different ways educational credentials are realized, which, it is argued, is a major basis for the maintenance of educational inequality.